Theoretical and Practical Aspects of Value Education - Vasiliauskas, Romanas (Acta Paedagogica Vilnensia, 2005)
The article treats the views of various scientists on the concept of values. Such values are treated as an interdisciplinary object which includes philosophical, psychological and pedagogical approaches. Findings suggest that value is one of the main parts of the educational structure, in which cognition, emotional and behavioural aspects are closely related in the valuing process. In the study of the aspects of value concepts a conclusion is made that value forms a whole of meanings. Various aspects of its meanings, such as negativeness and positiveness, as well as objective and subjective demand character of values are revealed. The process of valuing is determined by such indicators as needs, interest, ideal, aims and beliefs. The study shows in what way these indicators affect the process of valuing.
Keywords: value; value orientation; cognition; knowledge; emotions; behavior